A novel GLUT-4 electrochemical immunosensor based on a poly(thionine)-gold nanoparticle nanocomposite: Combining complex capacitance and dissolved oxygen to obtain an analytical signal - Olean-Oliveira, André; Seraphim, Patrícia Monteiro [UNESP]; Portugal, Miquéias L. [UNESP]; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2025)
Detection of glucose transporter 4 (GLUT4) is essential for understanding various physiological and pathological processes. This work reports the development of a novel electrochemical immunosensor for the direct detection of GLUT4, employing dissolved oxygen as a redox probe. This molecular oxygen-sensitive response is mediated by a redox-conductive polymer based on thionine. The sensor platform was fabricated via a one-step electropolymerization of thionine and gold nanoparticles (AuNPs) onto a platinum screen-printed electrode (Olean-Oliveira et al., 2022a). The immunosensor was then constructed by physical adsorption of a GLUT4 antibody onto the poly(thionine)-AuNP composite surface. This label-free approach eliminates the need for secondary antibodies or enzymes. The immunosensor performance was evaluated using electrochemical impedance spectroscopy (EIS). The sensing mechanism relies on impedance changes; increasing GLUT4 concentrations lead to increased impedance due to enhanced surface blocking upon GLUT4-antibody binding. This interaction impedes oxygen diffusion to the polymer redox sites, resulting in increased electrical resistance. Analysis of the redox capacitance as a function of frequency demonstrates a decrease in the capacitive arc with increasing GLUT4 concentration.
Keywords: Anti-GLUT4; Electrochemical impedance spectroscopy; Glucose transporters; Gold nanoparticle polymer; Immunosensor; Physiological protocol